Neutrophils alter epithelial response to Porphyromonas gingivalis in a gingival crevice model - Bondy-Carey, Jessica L. (2012)
A gingival crevice model (epithelial cell- Porphyromonas gingivalis – neutrophil) was established and used to profile gingipain, matrix metalloproteinase, MMP mediators (NGAL and TIMP-1) and cytokine networks. Smoking is the primary environmental risk factor for periodontitis. Therefore, the influence of cigarette smoke extract (CSE) was also monitored in the same model. P. gingivalis alone induced low levels of IL-1β and IL-8 from epithelial cells, but high levels of both cytokines were produced on the addition of neutrophils. CSE-exposure (100 and 1000 ng/ml nicotine equivalency) significantly compromised P. gingivalis-induced cytokine secretion (both p < 0.05). P. gingivalis induced impressive secretion of NGAL (p < 0.05) which was not influenced by CSE. The influence of CSE on gingipains production was strain-specific. Purified gingipains effectively and rapidly degraded both TIMP-1 and MMP-9. Induction of large amounts of NGAL, degradation of TIMP-1, and increased gingipain activity would each be expected to prolong collagen degradation and promote disease progression. However, gingipains also degrade MMP-9. Thus, P. gingivalis exerts a complex influence on the proteolytic balance of a gingival crevice model. CSE-exposure reduces the pro-inflammatory cytokine burden, which may be expected to promote P. gingivalis survival. In addition to novel findings that provide mechanistic insight into periodontal disease progression, these results are in keeping with the recognized clinical dogma of decreased inflammation / increased disease in smokers. Thus, this straightforward gingival crevice model is established as a suitable vehicle for the elucidation of mechanisms that contribute to susceptibility to periodontitis.